Harmonisasi Hubungan Etnis Tionghoa dan Etnis Bali di Kintamani: Kajian Kritris Terhadap Multikultur dalam Masyarakat Bali - I Ketut Setiawan (Journal Social and Humaniora, 2022)
One of the ethnic groups in Bali, apart from the Balinese ethnicity, is the Chinese. From arhaeological evidende, it can be seen that since the seventh century, Chinese ethnicity has existed in Bali. The ethnic Chinese who live in harmony with the Balinese are interesting to be studied, because outside Bali, this ethnic relationship shows a tendency to be disharmonious and conflicts often lead to violence. The exixtence of Chinese ethnic in Kintamani is interesting to be studied because the two ethnic group in. Kintamani knit a harmonious relationship, so as to create a harmonious life. The purpose of this study is to deconstruct social phenomena so that they can understand the various reasons that cause the two ethnic groups to live side by side in harmony. This study uses a qualitative descripte method with a critical ethnographic approach in the perspective of cultural science. Data were collected by observation, interviews, and document studies. The data were analyzed qualitatively by using critical social theory. The results of the study indicate that the harmonious relationship between ethnicities occurs because there is power and capital played by both ethnicities, in addition to historical and cultural factors.